The use of scaffolding strategies to improve reading aspects among students of tenth year of educación general básica morning session, at unidad educativa comunitaria intercultural bilingüe guardiana de la lengua y saberes “tupak yupanki”, in the canton of Saraguro, province of Loja during 2020-2021 school year. - González Poma, Cristian Alvino (2021)
The objective of this research was to improve reading aspects through the use scaffolding strategies among students of tenth year of Educación General Básica morning session, at Unidad Educativa Comunitaria Intercultural Bilingüe Guardiana de la Lengua y Saberes “Tupak Yupanki”, in the Canton of Saraguro, province of Loja during 2020-2021 school year. The scientific, the descriptive, the statistical and the analytical-synthetic methods were adopted to gather, describe, process, analyze, and interpret the obtained results. Tests and questionnaires were the main instruments applied to collect data of 16 students. Similarly, observation sheets and field notes were used to record the behavior and attitude of the students’ progress. The results indicated that scaffolding strategies improved in an acceptable way the students' reading aspects such as phonics, phonemic awareness, vocabulary and comprehension. Scaffolding strategies enabled students to be responsible and motivated them to participate in the process of reading more actively and independently